2023
DOI: 10.3390/drones7030180
|View full text |Cite
|
Sign up to set email alerts
|

Collision-Free 4D Dynamic Path Planning for Multiple UAVs Based on Dynamic Priority RRT* and Artificial Potential Field

Abstract: In this paper, a four-dimensional (4D) dynamic cooperative path planning algorithm for multiple unmanned aerial vehicles (UAVs) is proposed, in which the cooperative time variables of UAVs, as well as conflict and threat avoidance, are considered. The algorithm proposed in this paper uses a hierarchical framework that is divided into a 4D cooperative planning layer and a local threat avoidance planning layer. In the cooperative planning layer, the proposed algorithm, named dynamic priority rapidly exploring ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…From Figure 14, it can be observed that due to the different locations and numbers of UAVs, the agent may determine different avoidance actions when facing collision risks, leading to different trajectories. DDQN is a typical value-based DRL algorithm [18,19], while APF utilizes the repulsive force of obstacles and the gravitational force of target to guide the UAV motion, and is widely used in research on collision avoidance [30,31]. DDQN requires that the agent action space be discrete, which is set to ∆𝜑 ∈ 3°, 0, 3° , ∆𝑍 ∈ 1 m, 0 m, 1 m , ∆𝑉 ∈ 2 m/s, 0 m/s, 2 m/s .…”
Section: Different Numbers Of Uavsmentioning
confidence: 99%
See 1 more Smart Citation
“…From Figure 14, it can be observed that due to the different locations and numbers of UAVs, the agent may determine different avoidance actions when facing collision risks, leading to different trajectories. DDQN is a typical value-based DRL algorithm [18,19], while APF utilizes the repulsive force of obstacles and the gravitational force of target to guide the UAV motion, and is widely used in research on collision avoidance [30,31]. DDQN requires that the agent action space be discrete, which is set to ∆𝜑 ∈ 3°, 0, 3° , ∆𝑍 ∈ 1 m, 0 m, 1 m , ∆𝑉 ∈ 2 m/s, 0 m/s, 2 m/s .…”
Section: Different Numbers Of Uavsmentioning
confidence: 99%
“…DDQN is a typical value-based DRL algorithm [18,19], while APF utilizes the repulsive force of obstacles and the gravitational force of target to guide the UAV motion, and is widely used in research on collision avoidance [30,31]. DDQN requires that the agent action space be discrete, which is set to ∆ϕ ∈ {−3 • , 0, 3 • }, ∆Z ∈ {−1 m, 0 m, 1 m}, ∆V ∈ {−2 m/s, 0 m/s, 2 m/s}.…”
Section: Comparison With Other Algorithmsmentioning
confidence: 99%
“…Potential field-based methods utilize attraction and repulsion forces to guide agents toward desired positions while avoiding collisions. Artificial potential functions [67] define a mathematical representation of the desired formation and drive the swarm toward it. Behavior-based methods focus on defining individual agent behaviors and interactions that collectively result in the desired formation.…”
Section: Swarm Formation Control Strategiesmentioning
confidence: 99%
“…Path planning consists of planning an optimal path from an initial position to an end position, with quad-rotor UAVs flying in the presence of obstacles on the terrain and the required constraints being met at the same time [10]. At present, the most common algorithms for path planning include Dijkstra's algorithm [11], the A* algorithm [12][13][14], the Artificial Potential Field Method [15], the RRT (Rapid-exploring Random Trees) algorithm [16][17][18][19][20], and the RRT* algorithm [21][22][23][24][25], the last of which is progressively optimized for the RRT algorithm.…”
Section: Introductionmentioning
confidence: 99%